The co-existence of Plasmodium: sidelights from falciparum and vivax malaria in Thailand. - Snounou, G; White, N (2004)
It is rare to find human populations exposed to a single malaria parasite species - in most endemic areas, at least three Plasmodium species co-exist. Here, we briefly review mixed species infection in malaria, and discuss apparently disparate clinical and epidemiological observations of Plasmodium falciparum and Plasmodium vivax, now equally prevalent in Thailand, which suggest that an 'entente cordiale' between these two species might be beneficial both to parasites and humans. If this were the case, the influence of changes in the parasite formula in endemic areas on the burden of malaria would become an important element of study.